Initial Coin Offerings as a Contemporary Financing Alternative: Successful Ways to Raise Funds - Ulrich, Klaus; Ribeiro-Soriano, Domingo; Garcia-Isla, Francisco Javier (IEEE transactions on engineering management, 2024)
Initial coin offerings (ICOs) have emerged as a modern alternative financing instrument capable of connecting economic agents, entrepreneurs, and investors from all over the world. The benefits of blockchain technology in terms of privacy, security, and immutability make these financing tools particularly attractive. In this article, we analyze ICOs through the world's largest global database of ICOs. The analysis has been carried out through fsQCA methodology to a sample of 75 projects funded through this funding tool and aims to answer what are the possible ways to achieve success in fundraising in an ICO. The results shed light on the importance of financial factors, such as the risk of the operation, but also related to communication and user communities for the success or failure of these campaigns. The aim of this article is to provide entrepreneurs with a tool to help them plan their ICOs, develop them in a suitable way to attract the largest amount of funds, and mobilize investors' resources, achieving a synergy between the entrepreneur and the investor, with impactful, innovative, and profitable projects. It is also intended to contribute to the academic development of the subject with comparative qualitative studies.